A life prediction method and damage assessment for creep-fatigue combined with high-low cyclic loading. (August 2022) - Li, Kai-Shang; Wang, Ji; Fan, Zhi-Chao; Cheng, Lv-Yi; Yao, Shu-Lei; Wang, Run-Zi; Zhang, Xian-Cheng; Tu, Shan-Tung
Highlights: Novel creep-fatigue combined with high-low cyclic loading tests were performed. Cyclic responses and damage distribution under various cyclic tests were compared. Multi-damage model was established to perform broad applicability in life prediction. A three-dimensional damage interaction diagram is proposed. Abstract: Many high-temperature rotating components are always subjected to complex loading waveforms, arising the concerns for various damage modes simultaneously. The aim of the present work is to propose an energy-based model to predict the creep-fatigue combined with high-low cyclic loading (CF-HL) life, wherein the interactions of low cycle fatigue (LCF) damage, high cycle fatigue (HCF) damage and creep damage on the CF-HL behaviors are considered together. In order to validate the prediction capabilities of the proposed model, strain-controlled LCF, creep-fatigue interaction (CFI) tests as well as the newly developed CF-HL tests in Inconel 718 superalloy are performed at 650 ℃. Results show that most of the experimental data points fall into a range within a scatter band of ± 2 on life prediction. In addition, a robust and flexible assessment method within three-dimensional damage interaction diagram is proposed with the extension of traditional creep-fatigue interaction diagram. Finally, a case study of a turbine fir-tree attachment is provided to illustrate the engineering meanings of the developed energy-based model and damage interaction diagram, which is expected to be promoted in many high-temperature components.